Bimetallic metal organic frameworks with precisely positioned metal centers for efficient H2 storage. Issue 86 (12th October 2018) - Kim, Daeok; Song, Kyung Seob; Buyukcakir, Onur; Yildirim, Taner; Coskun, Ali
Abstract : Predesigned metal clusters for ordered heterogeneity in MOFs. Abstract : We demonstrated that the ratio and position of two different metal ions, Pd and Cu, can be precisely controlled within MOFs through predesigned metal clusters. These MOF structures incorporating Pd–Cu paddle wheel units were synthesised simply by reacting Pd–Cu acetate metal clusters and tritopic organic linkers at room temperature. Pd–Cu open metal sites were found to be uniformly distributed throughout the MOFs with a ca. 1 : 1 ratio. The incorporation of Pd into the MOF structure also led to enhanced affinity towards H2 with Q st values up to 8.9 kJ mol −1 .